Agen46 Business Unit Mechanism and Improvements in PT. Bank Negara Indonesia UGM Branch Office - Ananta, Rafi Raditya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This internship thesis explores the Agen46 mechanism and improvement in Bank Negara Indonesia (BNI) KC UGM Yogyakarta and the potential for its further development through the integration of new technology. Agen46 is a business unit mechanism that enables third-party agents to provide banking services to customers on behalf of the bank. The objective of this study is to analyze the current state of the Agen46 mechanism, identify potential challenges and opportunities, and propose strategies for improvement. To achieve this objective, this research employs qualitative methods including interviews with BNI officials and Agen46 agents, as well as observation of the Agen46 process in action. The study found that the Agen46 mechanism has been successful in expanding BNI's reach and increasing its customer base, particularly in rural areas where traditional banking services are not readily available. To address these challenges, the study proposes several strategies for improvement, including the adoption of new technology such as Electronic Data Capture (EDC) and the establishment of stronger partnerships with local potential businesses. These strategies aim to enhance the efficiency and effectiveness of the Agen46 mechanism, improve customer satisfaction, and increase profitability for both BNI and its Agen46 agents. The study also highlights the potential for cooperation agreements between BNI and potential stores to activate Agen46 in more locations, as well as the development of a loyalty program to incentivize Agen46 agents to increase their performance and expand the reach of the mechanism. These proposals aim to address the challenges faced by the Agen46 mechanism and position it for sustainable growth and success in the future.